Social Media in Journalism practice - La Rosa, Amaro (2014)
The article presents one panoramic viewpoint on social media influence in the work of professional journalism. The use of social media as information sources and their impact on information processing and news production routines are described. It is concluded that social media influence growing in the journalistic activity that becomes effective in contemporary society.